Effects of electrode area and interval on the sensitivity of bilateral silicon detectors used for neutron dosimetry. (December 2018) - Huang, Y.H.; Yu, M.; Zhang, Z.; Wang, J.X.; Zhao, X.Y.; Zhu, Z.Y.; Hu, A.Q.; Liu, J.L.; Wang, J.Y.; Jin, Y.F.; Zhou, C.Z.
Abstract: In this study, we investigated the effects of the electrode area and interval on bilateral silicon detectors in order to improve the neutron dose sensitivity while also considering the current density. The voltage–current and sensitivity–current characteristics of PIN diodes were measured experimentally. Detectors were fabricated with different electrode intervals and electrode areas, and the effects of these structural parameters on the detector sensitivity were investigated. We found that the sensitivity at 1.0 mA could be improved to 1170 mV/Gy by using an electrode interval of 4000 μm and an electrode length of 600 μm. Thus, we demonstrated the feasibility of achieving high sensitivity with a thin detector. Highlights: Effects of electrode area and interval on sensitivity of bilateral silicon detectors. Diodes are exposed to neutron radiation for sensitivity testing. Detectors fabricated with different electrode intervals and electrode areas. Feasibility of achieving high sensitivity with a thin detector was demonstrated.